Probes for the study of icy and subglacial environment of planets - A. V. Zelenchuk; V. A. Krylenkov (Лëд и снег, 2019)
The article proposes a technology for increasing the thermic ice drilling rate under the influence of hydraulic force generated by the probe (or cryobot), which increases the coefficient of conversion of thermal energy into the energy of ice melting and allows increasing the power of thermal head of the probe. A single-wire Tesla system is proposed to use for the probe power supply, which makes it possible to reduce the volume of the cable and losses of transmitted energy. The method of the probe self-lifting to the ice surface without using the hydraulic force (traction), i.e. without a load on the cable, is proposed. To study thick (up to 5 km) ice sheets and subglacial water environments on the Earth, as well as the ice cover (up to 30 km thick) and the subglacial ocean of the Europe (the Jupiter’s satellite), conceptual principal designs of the probe (or cryobot) have been developed on the basis of thermic-hydraulic drilling (THD). Implementation of the THD‑cryobot designs will allow organizing systemic studies of glaciers and subglacial water environments on the Earth and other planets, not disturbing their ice isolation with multiple savings of financial and technical means, energy and time.